Utilization of allostatic load index (ALI) to evaluate stress during weaning of beef cattle - Meyer, Sara, author; Manriquez Alvarez, Diego, advisor; Pinedo, Pablo, committee member; Holt, Timothy, committee member (Colorado State University. Libraries, 2025)
Allostatic load index (ALI) has been utilized for years in human populations, and more recently in primate and wild animal populations, to predict the longevity and future health status of individuals. The purpose of this study was to apply the principles of allostatic load to assess beef cows' weaning stress as the principal factor. Two different weaning treatment groups, traditional abrupt or fence-line weaning strategies, were applied to cows. Stress levels were determined by measuring plasma cortisol, DHEA, TNF-α, and IL-6 concentrations through ELISA (enzyme-linked immunosorbent assay) over the course of a 64-day study period. Cows in the fence-line weaning treatment were found to have significantly decreased plasma TNF-α (2.83 pg/ml and 3.44 pg/ml ± 0.30; p=0.04) levels and ALI scores (1.12 and 1.87 ± 0.37; p-0.05) as compared to the abruptly weaned treatment group. The results from this study support that fence-line weaning of calves decreases the stress levels of cows following weaning. Additionally, there is evidence that cows with calves weaned via fence-line weaning have an increased longevity projection.
Keywords: beef cattle; allostatic load; weaning